Estabilidade assintótica para um modelo dissipativo de equação de placas com p - Laplaciano e termo memória - Paciência, Alan Kardec Reis (2017)
In this work, we study situations involving the existence, uniqueness, decay rates and asymptotic behavior of solutions for a class of nonlinear equations cards and memory. In particular, in the first chapter we review some issues related to a number of results derived from the general theory of functional analysis, which will be applied during this dissertation. The next chapter will discuss an equation of the fourth order dissipative plate with nonlinear perturbations of type p - Laplacian and locally Lipschitz and memory. Continuing, we prove the exponential stability of energy corresponding to the homogeneous problem with second-order term of memory.